PENGARUH FINANCIAL LEVERAGE, KINERJA KEUANGAN DAN ENVIRONMENTAL SOCIAL AND GOVERNANCE (ESG) TERHADAP NILAI PERUSAHAAN - Syahwallistiana, Nandita; Yusuf, Nur’aini (Jurnal Nusa Akuntansi, 2025)
This study aims to obtain empirical evidence on the effect of financial leverage, financial performance and Environmental, Social and Governance (ESG) on firm value. This type of research uses associative quantitative research using secondary data taken from the IDX website and the websites of company listed on the Indonesia Stock Exchange for the period 2019 to 2023. The sampling method used in this study is to use the non-probability sampling method with the sampling technique chosen is purposive sampling. The samples in this study were 9 companies with a total observation of 45 samples. Hypothesis testing was carried out using the E-views 12 application. The results of the data analysis show that partially financial performance and ESG do not affect the company's value, while financial leverage affects the company's value. And simultaneously financial leverage, financial performance and Environmental, Social and Governance (ESG) affects on the company's value.